Calvyn oor die koninkryk van God en die staat - Plooy, A. le R. du (Hervormde teologiese studies, 1992)
Calvin on the kingdom of God and the state This article focuses on the relationship between the kingdom of God and the state. An attempt is made to put into perspective Calvin’s distinction between the spiritual dominion (regnum spirituale) and the political dominion (regnum politicum). According to Calvin these two kingdoms should be distinguished and understood in the light of the kingdom of God. It is argued that the political dominion should seek to serve the kingdom of God in its own sphere. Secular governments should therefore establish and preserve civil justice and order so that God can be glorified.